Tubercular splenic abscess and recurrent acute on chronic tubercular pancreatitis: a rare coincidence in an immune competent child - Acharyya, Saugata; Acharyya, Kakoli (International Journal of Contemporary Pediatrics, 2020)
Tubercular splenic abscess in association with chronic tubercular pancreatitis is scarcely reported in an immune competent child. 12 years old boy had presented with recurrent attacks of upper abdominal pain radiating towards left shoulder. He had multiple hospitalizations with similar complaints. The child had associated anorexia and significant weight loss during the period of his illness. Clinical examination revealed tenderness and muscle guard over the epigastric region. The pancreatic enzymes were markedly raised. Abdominal CT scan had suggested chronic pancreatitis with multiple splenic abscesses. The cartridge- based nucleic acid amplification test (CBNAAT) of the pus aspirated from the abscess confirmed the presence of pan sensitive mycobacterium tuberculosis. Image guided fine needle aspiration biopsy revealed the presence of caseating granulomatous lesion. Treatment with anti-tubercular drugs led to complete clinical recovery and normalization of pancreatic enzymes at follow up. An immunocompetent child had chronic tubercular pancreatitis associated with tubercular splenic abscess.